2001
DOI: 10.1002/jemt.1081
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic inflammation in the context of migraine

Abstract: Despite considerable research into the pathogenesis of idiopathic headaches, such as migraine, the pathophysiological mechanisms underlying them remain poorly understood. Although it is well established that the trigeminal nerve becomes activated during migraine, the consequences of this activation remain controversial. One theory, based on preclinical observations, is that activation of trigeminal sensory fibers leads to a painful neurogenic inflammation within the meningeal (dural) vasculature mediated by ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(151 citation statements)
references
References 81 publications
4
144
0
3
Order By: Relevance
“…Thus, BIBN4096BS could produce, at a postjunctional level (by CGRP receptor blockade), effects similar to those that triptans cause by reducing CGRP release, and that result in inhibition of CGRP receptor signalling. Indeed, triptans inhibit trigeminal CGRP release in animal experimental models [55,63], and clinical data show that sumatriptan normalised the elevated CGRP levels with alleviation of migraine [55] and cluster headache attack [65]. These findings have suggested that BIBN4096BS could be developed as an effective antimigraine drug.…”
Section: Cgrp Antagonists In Migrainementioning
confidence: 98%
See 1 more Smart Citation
“…Thus, BIBN4096BS could produce, at a postjunctional level (by CGRP receptor blockade), effects similar to those that triptans cause by reducing CGRP release, and that result in inhibition of CGRP receptor signalling. Indeed, triptans inhibit trigeminal CGRP release in animal experimental models [55,63], and clinical data show that sumatriptan normalised the elevated CGRP levels with alleviation of migraine [55] and cluster headache attack [65]. These findings have suggested that BIBN4096BS could be developed as an effective antimigraine drug.…”
Section: Cgrp Antagonists In Migrainementioning
confidence: 98%
“…Trigeminal nuclei as well as non-myelinated trigeminal sensory nerve fibres express an abundant CGRPlike immunoreactivity and cerebral blood vessels are innervated by sensory nerves that store several neuropeptides amongst which CGRP is the most abundant [63]. A Ca 2+ -dependent and capsaicin-sensitive release of CGRP, but not SP, has been documented from human tissues containing non-trigeminal [13] or trigeminal [11] sensory nerve endings.…”
Section: Migraine and Neurogenic Inflammationmentioning
confidence: 99%
“…The trigeminal nerve contains sensory and motor components but the sensory component, in particular, appears to be associated with migraine pathophysiology (Williamson and Hargreaves, 2001;Borsook, Burstein, Moulton and Becerra, 2006).…”
Section: The Trigeminovascular System In Migrainementioning
confidence: 99%
“…Migraine has long been considered a vascular headache (Wolff, 1948;Lance, 1993;Williamson and Hargreaves, 2001). Dilatation of extracranial vessels during attacks (Drummond and Lance, 1983;Iversen, Nielsen, Olesen and Tfelt-Hansen, 1990) may be mediated, at least in part, by release of CGRP from trigeminal nerve terminals as levels were found to be elevated in the external jugular vein (Goadsby, Edvinsson and Ekman, 1990).…”
Section: The Trigeminovascular System In Migrainementioning
confidence: 99%
“…This agent is an efficient non-narcotic pain killer with intermediate anti-inflammatory effect. Therefore consider as a preferable option for pain management of different type of primary headache cases admitted to the ED (16)(17)(18)(19). Current study was conducted with the aim of ketorolac efficacy measurement as a non-narcotic antiinflammatory pain killer agent for controlling the primary headache in of patients presented to the ED with all types of primary headaches.…”
Section: Introductionmentioning
confidence: 99%